Brooks Range Treeline White Spruce Needle Nutrients and Stable Isotopes (2019-2022) - Patrick Sullivan; Rebecca Hewitt; Colin Maher; Roman Dial (Arctic Data Center, 2023)
Measurements of treeline white spruce needle carbon, nitrogen and phosphorus concentrations, along with stable isotopes of carbon and nitrogen. Samples were collected of the most recent needle cohort at breast height in August and September. The purpose of this dataset was to examine spatial variation in white spruce needle nutrition and gas exchange physiology across the Brooks Range and in relation to local microclimates. The 2021 and 2022 datasets contain data for treeline trees that were treated with NPK fertilizer at a sub-set of the research sites.